Associations de migrants et coopération internationale Agriculture et développement durable au Sénégal - Maggi, Jenny (Terrains des sciences sociales, 2022)
Since the global food crisis of 2008, Senegalese migrant associations have become involved in the agricultural development of their localities of origin. Through their projects they have created a transnational dynamic characterized by the circulation of goods, innovations, and skills between the host and the origin areas. This book analyses a series of associative projects initiated by Senegalese migrants in three European countries, France, Switzerland, and Italy. These countries differ in terms of policies aimed at supporting and recognizing migrant and diaspora associations in their role as actors of development cooperation. Significantly, the comparison gives insight into whether factors specific to each host context have an impact on the associative dynamics and on the characteristics of the projects in terms of sustainable agricultural development. Such an analysis is also useful for other host and home countries. The core findings aim to enrich the current debate on the links between migration and development, which is taking place from the global to the local level among researchers, international organizations, state actors, NGOs, as well as migrant and diaspora associations.